P020 Comparison of the aptima mycoplasma genitalium tma assay and the fasttrack diagnostics (FTD) urethritis basic assay for detection of M. genitalium in gum specimens. (8th June 2017) - Cliff, Penny; Vidican, Cristina; Hassan-Ibrahim, Mohammed; Ovens, Katie; Wilson, Andrea; White, John; O'Shea, Siobhan; Soni, Suneeta
Abstract : Introduction: Testing for M. genitalium in the UK is limited and detection has relied on realtime PCR assays. The Hologic Aptima Mycoplasma genitalium TMA assay for use on the Panther® system is now available. This study compared a commercial realtime PCR and the Aptima assay using stored clinical specimens. Methods: Clinical specimens (76 urines, 33 vaginal swabs, 2 rectal swabs, 1 pooled sample and 2 unknowns) from men with urethritis and women with pelvic inflammatory disease were tested for M. genitalium DNA using the FastTrack Diagnostics (FTD) Urethritis Basic assay. Residual specimen was then transferred to an Aptima urine tube and tested for the presence of M. genitalium ribosomal RNA using the Aptima TMA assay. Results: Of the 113 specimens tested, 24 (21%) were positive and 87 (77%) negative on both assays. There were two discrepant results (1.7%) in urine specimens that were positive on the Aptima TMA assay and negative on the FTD Urethritis assay. One was confirmed as positive by the Reference Laboratory using their in-house MgPa PCR, indicating a false negative result on the FTD Urethritis assay. The other discrepant result was low level positive on the Aptima TMA assay and negative at the Reference Laboratory. Discussion: 98% of samples gave concordant results, indicating that both assays are appropriate for use in clinical service. However, the additional positive detected by the Aptima assay, explained by detection of target in multiple copies in each bacterial cell, suggests that this assay is more sensitive.